An experimental study on transporting a free-float capable tension leg platform for a 10 MW wind turbine in waves. (December 2021) - Mas-Soler, Jordi; Uzunoglu, Emre; Bulian, Gabriele; Guedes Soares, C.; Souto-Iglesias, Antonio
Abstract: The paper presents the towing tests of CENTEC-TLP, a state-of-the-art free-float capable tension leg platform supporting a 10 MW wind turbine. The platform's design process and the overall dynamic behaviour was previously described in the literature. This work focuses on the platform's transportation stage, which is designed to have a shallow draft and certain characteristics resembling blunt bodies such as barges. The hydrodynamic behavior of this hull form in calm water and waves is investigated experimentally. The results are compared with similar relevant data available in the literature. As for added resistance in waves, the influence of wave characteristics and speed are evaluated. It is found that some of the cases display a reduction of average resistance in waves compared to calm water. Finally, the dynamic behaviour of the system in two relevant sea states is assessed with reference to risk of excessive motions during transport. Highlights: Towing tests in calm water and waves of a floating wind turbine carried out. The floater is a state-of-the-art free-float capable TLP with a 10 MW turbine. Results are compared with similar relevant data available in literature. Behaviour in two relevant sea states assessed with reference to risk of excessive motions. Some cases display reduction of average resistance in waves compared to calm water.